2019
DOI: 10.3390/ijerph16173153
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Practice-Level Performance Indicators in Primary Health Care in Hungary: A Nationwide Cross-Sectional Study

Abstract: The performance of general practitioners (GPs) is frequently assessed without considering the factors causing variability among general medical practices (GMPs). Our cross-sectional national-based study was performed in Hungary to evaluate the influence of GMP characteristics on performance indicators. The relationship between patient’s characteristics (age, gender, education) and GMP-specific parameters (practice size, vacancy of GP’s position, settlement type, and county of GMP) and the quality of care was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…Rather, the free choice of GPs in Hungary, which results in shifting patients from less to more intensive care, may be responsible for this finding. The negative influence of retirement, age of GP and the positive influence of more specialized (adults only) GMPs are in good concordance with the published observations [37,64,65].…”
Section: Main Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Rather, the free choice of GPs in Hungary, which results in shifting patients from less to more intensive care, may be responsible for this finding. The negative influence of retirement, age of GP and the positive influence of more specialized (adults only) GMPs are in good concordance with the published observations [37,64,65].…”
Section: Main Findingssupporting
confidence: 90%
“…Moreover, GP interventions reduce the disadvantage some social groups have in access to higher tech medical treatments. The effect of the size of a general medical practice (GMP) on health outcome and spending was inconclusive in international studies [36][37][38]. Additionally, the age, gender and vacancy of a GP seems to have only limited effect [37,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous domestic research have shown that the quality of primary care varied by the structural characteristics of GMPs in the prepandemic period [ 27 , 28 , 29 ]; therefore, we hypothesized the same during the pandemic period. However, GMP attributes had no remarkable role, suggesting that adjustment for these factors is not important in general mortality monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…GPs had to organize vaccination-related tasks in parallel with the maintenance of primary care adapted to pandemic circumstances. Because the quality of primary care varied by the structural characteristics of the general medical practices (GMPs) in the prepandemic period [ 27 , 28 , 29 ], the quality of this adapted care probably operated with variability in the pandemic period as well.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, several MAEIs have been implemented in Hungary. In 2009, the National Health Insurance Fund (NEAK) established an indicator system for primary healthcare, which directly targets medication adherence ( Kovács et al, 2019 ; NEAK, 2019 ). The system provides financial incentives for general practitioners (GPs) who reach the desired target values.…”
Section: Resultsmentioning
confidence: 99%